Kandungan Antioksidan Dan Serat Pangan Total Pada Bakso Daging Sapi Dengan Penambahan Serbuk Pegagan - Bestina, Afrida Arayani; Muhlishoh, Arwin; N, Nastitie Cinintya (Media Gizi Ilmiah Indonesia, 2023)
An increase in free radicals that is not accompanied by an increase in antioxidant intake will cause oxidative stress. Foods that contain lots of antioxidants and high fiber are recommended for people with type 2 DM because they can improve blood glucose control. Gotu kola powder is an herbal plant that has an active substance in the form of asiatic acid as an antioxidant and a source of dietary fiber. This study aims to determine effect of adding various formulations of gotu kola powder on antioxidant substance and total dietary fiber in beef meatballs as an alternative food for type 2 DM. This type of research is quantitative with experimental design. The research design used was a Completely Randomized Design (CRD) with a concentration of gotu kola powder in making beef meatballs, those were F0 (0%), F1 (5%), F2 (10%), and F3 (15%). This study found that the addition of gotu kola powder to beef meatballs had a significant effect on antioxidant content, insoluble dietary fiber, soluble dietary fiber, total dietary fiber, and organoleptic with p value = 0.000. Meanwhile, the hedonic quality with the aftertaste attribute had no significant effect (p=0.414). Selected product is F3 which has an antioxidant content of 27.19% and contains 3.96 in 100 g of beef meatballs. Selected product fulfills 26.4% of fiber requirement per one meal in the general group. There was a significant effect with the addition of gotu kola powder on the antioxidant content and total dietary fiber in beef meatballs.